A new active antimicrobial peptide from PD‐L4, a type 1 ribosome inactivating protein ofPhytolacca dioica L.: A new function of RIPs for plant defence?. Issue 19 (20th August 2015) - Pizzo, Elio; Zanfardino, Anna; Di Giuseppe, Antonella M.A.; Bosso, Andrea; Landi, Nicola; Ragucci, Sara; Varcamonti, Mario; Notomista, Eugenio; Di Maro, Antimo
Abstract : We investigated the antimicrobial activity of PD‐L4, a type 1 RIP from Phytolacca dioica . We found that this protein is active on different bacterial strains both in a native and denatured/alkylated form and that this biological activity is related to a cryptic peptide, named PDL440–65, identified by chemical fragmentation. This peptide showed the same antimicrobial activity of full‐length protein and possessed, similarly to several antimicrobial peptides, an immunomodulatory effect on human cells. It assumes an alpha‐helical conformation when interact with mimic membrane agents as TFE and likely bacterial membranes are a target of this peptide. To date PDL440–65 is the first antimicrobial peptide identified in a type 1 RIP. Abstract : Several cationic enzymes are source of antimicrobial peptides. Cytoplasmic membranes are targets of most of antimicrobial peptides. In this study we report the first cryptic antimicrobial peptide from a type 1 RIPs. This peptide assumes a peculiar conformation in presence of membrane mimic agents.